2003
DOI: 10.1128/jvi.77.12.7007-7016.2003
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Infection Inhibits Tumor Necrosis Factor Alpha (TNF-α) Signaling by Targeting the 55-Kilodalton TNF-α Receptor

Abstract: Infection with human cytomegalovirus (HCMV) results in complex interactions between viral and cellular factors which perturb many cellular functions. HCMV is known to target the cell cycle, cellular transcription, and immunoregulation, and it is believed that this optimizes the cellular environment for viral DNA replication during productive infection or during carriage in the latently infected host. Here, we show that HCMV infection also prevents external signaling to the cell by disrupting the function of TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 50 publications
3
76
0
3
Order By: Relevance
“…This is often achieved through direct interaction between viral proteins and key cellular regulatory proteins (Fortunato et al, 2000). Similarly, HCMV can also alter cell signalling pathways by targeting cellular receptors (Fairley et al, 2002;Baillie et al, 2003). However, the mechanisms by which this occurs are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is often achieved through direct interaction between viral proteins and key cellular regulatory proteins (Fortunato et al, 2000). Similarly, HCMV can also alter cell signalling pathways by targeting cellular receptors (Fairley et al, 2002;Baillie et al, 2003). However, the mechanisms by which this occurs are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…HCMV can also interfere with the expression of a number of cellular receptors that are involved in receptor-mediated cell signalling. For instance, expression of both the tumour necrosis factor 1 receptor (TNFR1) (Baillie et al, 2003) and the epidermal growth factor receptor (EGFR) (Fairley et al, 2002) is repressed by HCMV infection. However, whilst HCMV disrupts TNFR1 expression by preventing transport of the receptor to the cell surface, it disrupts EGFR expression by reducing total steady state levels of EGFR RNA, probably by inhibition of transcription (Beutler et al, 2003;Fairley et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…La deleción del gen M36 hace a las cé-lulas infectadas con CMV murino susceptibles a la acción de los macrófagos, lo cual le confiere el potencial de ser un blanco terapéutico para pacientes inmunodeprimidos. Por otro lado, interfiriendo también con la apoptosis por la vía de los receptores, se ha observado que monocitos no infectados son capaces de incrementar la liberación de TNF al medio extracelular en presencia de células infectadas, aunque por su parte el virus disminuye la expresión de TNFR1 en la superficie de la célula infectada como otro mecanismo anti-apoptótico 28,29 .…”
Section: Inhibición De La Apoptosis Por CMVunclassified
“…In addition, HCMV infection in tumor cells may enhance tumorgenecity of these cells by increasing AKt activity (cellular protein kinase B) via activation of P13-K pathway and alteration in cellular metabolism and inhibition of apoptosis [88]. HCMV-IE2 mediates apoptotic control in HCMV retinitis by upregulating the expression of cellular FLICE-inhibitory protein [89][90][91]. Baillie et al have previously shown an anti-apoptotic effect of HCMV in Glioblastoma cells by induced reduction in TNF receptor-1 expression and consecutively inhibition of TNF-alpha signaling [89].…”
Section: Promotion Of Tumorigenesis By Human Cytomegalovirus (Hcmv) Imentioning
confidence: 99%
“…HCMV-IE2 mediates apoptotic control in HCMV retinitis by upregulating the expression of cellular FLICE-inhibitory protein [89][90][91]. Baillie et al have previously shown an anti-apoptotic effect of HCMV in Glioblastoma cells by induced reduction in TNF receptor-1 expression and consecutively inhibition of TNF-alpha signaling [89]. Moreover, expression of HCMV-US2 and US11 gene products in tumor cells may protect these cells from immune recognition and NK cell-mediated killing by down regulating expression of HLA-I and HLA-II [92].…”
Section: Promotion Of Tumorigenesis By Human Cytomegalovirus (Hcmv) Imentioning
confidence: 99%